Improved procedure for Brown's Class III maxillary reconstruction with composite deep circumflex iliac artery flap using computer-assisted technique. Issue 1 (1st January 2021) - Zhang, Wen-Bo; Soh, Hui Yuh; Yu, Yao; Guo, Chuan-Bin; Yu, Guang-Yan; Peng, Xin
Abstract: Reconstruction of Brown's Class III maxillary defect can be challenging due to the complex geometry of maxilla. We aimed to introduce an improved method for maxillary reconstruction with a composite deep circumflex iliac artery (DCIA) flap aided by virtual surgical planning and intraoperative navigation. A 27-year-old woman diagnosed with left maxillary fibromyxoma was admitted to our institution in December 2018. Pre-operative facial and iliac computed tomography data were obtained for virtual surgical planning. Personalized cutting template, tooth-supported surgical guide, and rapid prototype model with reconstructed orbital floor were printed for pre-operative preparation. Surgery was completely guided by the intraoperative navigation system. The root mean square estimate of the reconstructed area was 3.68 mm. The average errors measured on the lateral and medial DCIA segments were 0.61 and 0.85 mm, respectively. Application of virtual surgical planning and intraoperative navigation could potentially enhance the reconstruction outcomes.